Pengaruh Asimetri Informasi Terhadap Partisipasi Anggaran: Kepribadian Otoritarian Pimpinan Sebagai Moderating Variabel - Wahyu Prasetyo (Universitas Kristen Krida Wacana, 2014)
ABSTRACTThis paper aims to investigate the effect of interaction between information asymmetry and otorirarians personal to budget participation. The paper sets out hypotheses on the associations effect of interaction between information asymmetry and otorirarians personal to budget participation. A survey sample from 139 managers from non go public company was collected. Multiple Regression analysis was the used to test the resulting hypothesis. The results show that there is effect to interaction between information asymmetry and otorirarians personal to budget participation significantlyKeywords: Asimetri Informasi, Otoritarian, Partisipasi